Using the Pythagorean theorem where:
b^2 = c^2 - a^2
Let x be the value for b.
x^2 = 13.7^2 - 5.2^2
= 187.69 - 27.04
=√160.65
= 12.67
Hence x = 12.67
2 3/20 ,2 9/20, 2 1/2,2 11/20,2 4/5
Answer:
y=(x+6)^5+3
Step-by-step explanation:
This expression is factored completely. However, if we foil, we can make it to it's original expression.
When you foil, you get:
![x^2-2x-3x+6](https://tex.z-dn.net/?f=%20x%5E2-2x-3x%2B6%20)
Simplify.
![x^2-5x+6](https://tex.z-dn.net/?f=%20x%5E2-5x%2B6%20)
Answer:
X^2 + 10 + 24
Step-by-step explanation: